Leverage, Firm Size, Likuiditas, Financial Distress, dan Aktivitas Hedging Dengan Instrumen Derivatif - Condronegoro, Azhar; Hasibuan, Henny Triyana (E-Jurnal Akuntansi, 2023)
This research aims to determine the effect of leverage, firm size, liquidity and financial distress on hedging activities in textile and garment subsector companies listed on the Indonesia Stock Exchange due to unstable exchange rate changes. The sample method used is purposive sampling with 65 observations collected during the 2017-2021 period. The secondary data used is obtained from the company's financial reports available on the website of the Indonesia Stock Exchange (IDX) and other sources. Data analysis was performed using logistic regression method. The findings of this research show that leverage does not have a significant influence on hedging activities, while firm size and financial distress have a positive influence on hedging activities, and liquidity has a negative influence on hedging activities. Keywords: Leverage; Firm Size; Liquidity; Financial Distress; Hedging Activities